Atipični simptomi in znaki gastroezofagealne refluksne bolezni - Tepeš, Bojan (Zdravniški vestnik, 2006)
Background Gastroesophageal reflux disease (GERD) is very common in developed world, with the prevalence of disease is between 6 and 20%. Pathologic reflux can provoke not only typical symptoms (heartburn and regurgitation) but also atypical symptoms and diseases of extraoesophageal organs (pulmonary, ENT, mouth). High prevalence of GERD in patients with unexplained chest pain, asthma, chronic cough, chronic laryngitis, hoarsness and dental erosions is not a proof of causality. GERD can cause these diseases with reflux of acid and pepsin into pharynx, lungs and mouth (reflux theory) or through vasovagal mechanisms (reflex theory). Conclusions Good therapeutic success with medical or operative treatment in early methodologically not well conducted studies has not been completely proven in double-blind placebo controlled studies. GERD is an ethyological reason for these extraoesophageal symptoms and diseases in an approximately one third of patients. With diagnostic modalitiesthat we have now, we cannot clearly define in which patient is GERD is an ethyologic factor or a contributer, before we start the treatment. In patients suspected of having GERD, there is therapeutic option of a trial withhigh dose of proton pump inhibitor for 3 to 6 months. In other patients with low clinical suspicion of GERD, 24-hour pH testing should be done first.
Keywords: Asthma; Astma; Chest Pain; Cough; Diagnosis; Gastroesophageal Reflux; Gastroezofagealni refluks; hripavost; Kašelj; Pljučna fibroza; prsna bolečina; Prsni koš, bolečina; Pulmonary Fibrosis; simptomi